THE SCIENTIFIC HERITAGE OF ACADEMICIAN UTKIR ISLOMOVICH ISLOMOV IN THE RESEARCH OF THE MOST ANCIENT PERIODS OF UZBEKISTAN - Akhmadalieva Ranokhan Orinboy kizi (Western European Studies, 2025)
This in the article Uzbekistan the most ancient periods in learning academic Sharp Islamovich Islamov's scientific activity, methodological approaches and archaeology to science added incomparable contribution analysis will be done. The scientist Paleolithic, Mesolithic, Neolithic and Eneolithic to the times related research based on Uzbekistan in the territory primitive society development main stages scientific in terms of covered. In the article Islamov by working issued periodization principles , paleolithic of cultures classification , archaeological of materials paleogeographic factors with related without analysis to be done wide open is given . Also, its scientific school, pedagogical activity and independence in the years scientific of the inheritance national in historiography importance illuminated . Research results Uzbekistan in archaeology primitive society history in learning important theoretical and methodological basis become service does.
Keywords: Sharp Islamovich Islamov; Uzbekistan archaeology; primitive society; paleolithic